Preliminary Findings of Adult Health Screening under National Health Insurance in Taiwan - Huang, L.; Tseng, H. M. (Methods of Information in Medicine, 2002)
Objectives: To provide baseline values of health elated parameters for the Taiwanese population.Methods: A systematic sample of 9016 out of 692,311 persons undergoing health check-ups is analyzed and described, and compared to a similar survey undertaken ten years ago. Some physical indices and lab tests exhibited significant age and sex related differences.Results: The prevalence of groups of diseases, and the distribution of test results by age and sex are reported and compared to other studies.Conclusions: Compared to the survey conducted ten years ago, Taiwanese adults are taller and heavier, but not necessarily healthier.
Keywords: Health status indicators; mass screening; health surveys; Taiwan